Bioactive Dietary VDR Ligands Regulate Genes Encoding Biomarkers of Skin Repair That Are Associated with Risk for Psoriasis - Amitis Karrys (Nutrients, 2018)
Treatment with 1,25-dihydroxyvitamin D3 (1,25D) improves psoriasis symptoms, possibly by inducing the expression of late cornified envelope (LCE)3 genes involved in skin repair. In psoriasis patients, the majority of whom harbor genomic deletion of LCE3B and LCE3C (LCE3C_LCE3B-del), we propose that certain dietary analogues of 1,25D activate the expression of residual LCE3A/LCE3D/LCE3E genes to compensate for the loss of LCE3B/LCE3C in the deletant genotype. Herein, human keratinocytes (HEKn) homozygous for LCE3C_LCE3B-del were treated with docosahexaenoic acid (DHA) and curcumin, two low-affinity, nutrient ligands for the vitamin D receptor (VDR). DHA and curcumin induce the expression of LCE3A/LCE3D/LCE3E mRNAs at concentrations corresponding to their affinity for VDR. Moreover, immunohistochemical quantitation revealed that the treatment of keratinocytes with DHA or curcumin stimulates LCE3 protein expression, while simultaneously opposing the tumor necrosis factor-alpha (TNFα)-signaled phosphorylation of mitogen activated protein (MAP) kinases, p38 and Jun amino-terminal kinase (JNK), thereby overcoming inflammation biomarkers elicited by TNFα challenge. Finally, DHA and curcumin modulate two transcription factors relevant to psoriatic inflammation, the activator protein-1 factor Jun B and the nuclear receptor NR4A2/NURR1, that is implicated as a mediator of VDR ligand-triggered gene control. These findings provide insights into the mechanism(s) whereby dietary VDR ligands alter inflammatory and barrier functions relevant to skin repair, and may provide a molecular basis for improved treatments for mild/moderate psoriasis.